Stream gradient investigation in the Bükkalja using interpolated surfaces - Vágó, János (Acta Geographica Debrecina Landscape & Environment series, 2010)
The geological, tectonic settings of an area can be examined with the analysis of drainage network. In the Bükkalja, the Miocene pyroclasts – mainly the welded ignimbrites – had taken decisive part in the evolution of drainage network. For the confirmation of their role, the breakpoints of stream profiles were analysed. However this method provides information only about the direct surroundings of the creeks. In the aim of getting informations about the areas between the streams, surfaces were interpolated from stream gradient data and analysed as stream gradient maps. The stream gradient data were calculated with Hack J.T.’s formula, but due to the false results it was necessary to modify this formula and to recalculate the values. According to the map interpolated from the modified stream gradient values, there is a clearly identifiable relationship between the location of the welded ignimbrites on the surface, and the gradient values. Areas with high values are on the eastern part of the study area, where these pyroclasts can be found, while in the west, where the surface is covered by less resistant rock types, the gradient values are much lower.